News media coverage of extreme risk protection order policies surrounding the Parkland shooting: a mixed-methods analysis - Rocco Pallin; Amanda J. Aubel; Christopher E. Knoepke; Veronica A. Pear; Garen J. Wintemute; Nicole Kravitz-Wirtz (BMC, 2021)
Abstract Background Following the 2018 mass shooting at Marjory Stoneman Douglas High School in Parkland, Florida, there was a dramatic increase in media coverage of extreme risk protection orders (ERPOs) and in state policy proposals for ERPO laws. This study documents the frequency of news coverage of ERPOs throughout 2018 and examines the narratives used by media outlets to describe this risk-based firearm policy. Methods Using a mixed-method descriptive design, we examine the frequency of national news media coverage of ERPO legislation in 2018, before and after the Parkland shooting, and analyze the content of news articles related to a sample of states that considered ERPO legislation after the shooting. Results We find a sharp increase in the frequency of articles related to ERPOs following the Parkland shooting and smaller increases in coverage surrounding ERPO policy proposals and other public mass shootings that year. Nearly three-quarters of articles in our content analysis mentioned the Parkland shooting. The news media often mentioned or quoted politicians compared to other stakeholders, infrequently specified uses for ERPOs (e.g., prevention of mass violence, suicide, or other violence), and rarely included evidence on effectiveness of such policies. More than one-quarter of articles mentioned a mass shooting perpetrator by name, and one-third of articles used the term "gun control." Conclusions This study describes the emerging public discourse, as informed by media messaging and framing, on ERPOs as states continue to debate and implement these risk-based firearm violence prevention policies.